MENGOPTIMALKAN TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN UNTUK MEMBANGUN KARAKTER KRISTIANI - Veronika Veronika; Kristianti, Kristina Mamma', Elsa Meni, Peniel (ADISAM PUBLISHER, 2025)
The development of technology has brought significant changes in various aspects of life, including in Christian Religious Education. The use of technology in religious learning can increase the effectiveness of delivering material, enrich learning methods, and help students understand Christian values more interactively. Various innovations, such as digital Bible applications, learning videos, virtual classes, and artificial intelligence (AI), provide opportunities for students to explore Bible teachings in a more modern way. However, the use of technology also has challenges, such as distractions, the spread of information that is not in accordance with Christian teachings, and the digital divide in some regions. Therefore, an optimization strategy is needed through digital literacy based on Christian faith, choosing the right platform, and monitoring its use. With a good strategy, technology can be a means to support the growth of students' faith and character in living their lives according to the teachings of Christ